Exploring the Impact of Lifestyle Choices on Consumptive Behavior - Lubanah, Aulia Ifah; Latief, Jamil (Universitas Negeri Padang, 2024)
This research aimed to determine the influence of lifestyle on the consumptive behavior of teenagers on Panggang Island. This research uses quantitative methods. The population in this research is teenagers on Panggang Island. The sample was selected using simple random sampling, applying the Slovin formula with a margin of error of 10%, and resulted in 94 samples. The data used includes primary and secondary sources. Primary data was collected directly through questionnaires using a Likert scale. The analysis used was simple linear regression and was carried out using SPSS 25. This research indicates that lifestyle significantly affects adolescents' consumptive behavior on Panggang Island, with the lifestyle variable providing an effective contribution of 79.1%. This identified that the more adolescents' lifestyles, the more consumptive their behavior will be, and vice versa.